CLEAN WATER: Water detoxification using innovative photocatalysts - V. Likodimos; Dionysiou, D.D.; P. Falaras (Reviews in Environmental Science and Biotechnology, 2010)
Environmental pollution abatement and especially the growing demand for clean water pose one of the most severe challenges worldwide. Besides the scarcity of water resources, the presence of hazardous chemicals with serious adverse health effects, even at extremely low concentrations, impose serious considerations for the quality of drinking water. The rapid evolution of nanoscale science and technology has dramatically expanded the materials' application potential towards radically new or multifunctional properties rendering nanotechnology an indispensable component in shaping modern environmental science. The nanoscale-perspective maintaining the integrity of the environment is currently the stimulus for the development of innovative and cost-effective functional materials and sustainable processes for water treatment and purification. The CLEAN WATER (EU FP7 collaborative project) aims at the development of an innovative and efficient water detoxification technology exploiting solar energy and nano-engineered titania photocatalysts in combination with nanofiltration membranes. In this approach, nanostructured titania with high UV-visible response will be synthesized and stabilized on nanotubular membranes of controlled pore size and retention efficiency as well as on carbon nanotubes exploiting their high surface area to achieve photocatalytically active nanocomposite membranes. Comparative evaluation of the UV-visible and solar light efficiency of the modified titania photocatalysts for water detoxification will be intensively investigated on various target pollutants ranging from classical water contaminants such us phenols, pesticides and azo-dyes to the extremely hazardous cyanobacterial toxins and emerging endocrine disrupting compounds in order to evaluate/optimize the materials performance and validate their competence on water treatment. Particular efforts will be devoted to the analysis and quantification of degradation products as well as their toxicity. All these will be the crucial components for the fabrication of innovative continuous flow photocatalytic-disinfection-membrane reactors for the implementation of sustainable and cost effective water treatment technologies based on nano-engineered materials. © Springer Science+Business Media B.V. 2010.